The ventricular-subventricular zone: a source of oligodendrocytes in the adult brain - Oscar Gonzalez-Perez (Frontiers Research Topics, 2014)
Demyelinating diseases are characterized by an extensive loss of oligodendrocytes and myelin sheaths from axolemma, which commonly result in disability in young adults. To date, there is no effective treatment against these neurological disorders. In the adult brain, there are neural stem cells (NSCs) that reside within a niche denominated ventricular-subventricular zone (V-SVZ) in the lateral wall of the cerebral ventricles. NSCs give rise to neurons and oligodendrocytes that help preserve cellular homeostasis. Growing evidence indicates that V-SVZ progenitor cells may represent an endogenous source of oligodendrocytes that can be useful to treat demyelinating diseases. This e-Book collected the most recent evidence regarding the mechanisms that modulate the proliferation, migration, quiescence, cell-fate choices and survival of oligodendrocyte precursors generated in the V-SVZ. Herein, we compiled information about the role of Sonic hedgehog, NMDA receptors, ErbB proteins, hemopressin, erythropoietin, osmolarity and microglia in the oligodendrocyte production. Some chapters also describe the role of oligodendrocyte precursors in the preservation of cellular homeostasis, aging and white matter repair. All these information is presented as novel research findings, short communications, and review articles, which were written by experts in the field of oligodendrocyte generation, myelin production and white matter re-myelination.